High-Skilled Migration and Agglomeration - Sari Pekkala; William R. Kerr; Caglar Özden; Christopher Parsons (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper reviews recent research regarding high-skilled migration. We adopt a data-driven perspective, bringing together and describing several ongoing research streams that range from the construction of global migration databases, to the legal codification of national policies regarding high-skilled migration, to the analysis of patent data regarding cross-border inventor movements. A common theme throughout this research is the importance of agglomeration economies for explaining high-skilled migration. We highlight some key recent findings and outline major gaps that we hope will be tackled in the near future.
Keywords: F15; F22; J15; J31; J44; L14; L26; O31; O32; O33; 330; migration; talent; diaspora; agglomeration